Scribble downregulation in adenomyosis compromises endometrial stromal decidualization by decreasing FOXO1 expression. Issue 1 (8th November 2021) - Peng, Yaoming; Liu, Xiaoxia; Jin, Zhixing; Liu, Haiou; Xu, Congjian
Abstract: STUDY QUESTION: Does Scribble (SCRIB) contribute to aberrant decidualization of endometrial stromal cells (ESC) in adenomyosis? SUMMARY ANSWER: SCRIB knockdown impairs decidualization of ESC by decreasing Fork-head box O1A (FOXO1) expression through the protein kinase B (AKT) and atypical protein kinase C (aPKC) activated pathways. WHAT IS KNOWN ALREADY: Stromal SCRIB is required for primary decidual zone formation and pregnancy success in mice. In our previous studies, decidualization was dampened in ESC isolated from adenomyosis patients, yet the underlying molecular mechanisms remain elusive. STUDY DESIGN, SIZE, DURATION: Eutopic endometrium tissue samples from diffuse adenomyosis and non-adenomyosis patients in proliferative, early-secretory and mid-secretory phase (n = 10 per phase for each group) were explored. In parallel, in vitro decidualization studies were carried out in ESC isolated from non-adenomyosis women (n = 8). PARTICIPANTS/MATERIALS, SETTING, METHODS: The endometrial SCRIB expression was analyzed using immunohistochemistry staining and western blot. Quantitative RT-PCR (qRT-PCR), western blot and immunofluorescence staining were used to explore the expression of SCRIB in ESC during in vitro decidualization. siRNA-mediated SCRIB knockdown followed by decidual markers expression analysis, flow cytometry for cell cycle analysis and phalloidin staining for morphological analysis were performed to examine the function of SCRIB in ESC decidualization. RNA-sequencing was performed to examine the SCRIB-mediated transcriptional changes in decidualized ESC (DSC). Rescue experiments using an AKT inhibitor MK2206 and aPKC inhibitor NSC37044 were used to investigate the signaling pathways through which could mediate SCRIB-regulated FOXO1 protein expression and ESC decidualization. MAIN RESULTS AND THE ROLE OF CHANCE: We found that the expression of SCRIB in the mid-secretory phase eutopic endometrial stroma of adenomyosis patients was significantly lower than that of non-adenomyosis. SCRIB knockdown reduced the expression of decidual markers, abrogated the epithelioid-like morphological changes, inhibited the mesenchymal-to-epithelial transitions process and promoted the cell cycle progression of ESC during in vitro decidualization. SCRIB knockdown-induced decidualization defects were attributed to a decrease in expression of transcription factor FOXO1, known to regulate decidualization. Furthermore, we found that SCRIB knockdown induced the aberrant activation of AKT and aPKC, which led to FOXO1 phosphorylation and degradation. Rescue assay confirmed that restoring the expression of FOXO1 effectively reversed the decidualization defects and cell cycle progression caused by SCRIB knockdown. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: In this study, it was demonstrated that SCRIB knockdown mediated the activation of AKT and aPKC, contributing to FOXO1 degradation and aberrant decidualization, however, the molecular link between AKT and aPKC signaling was not determined, and still requires further exploration. WIDER IMPLICATIONS OF THE FINDINGS: Our findings support the hypothesis that adenomyosis interferes with embryo implantation due to insufficient endometrial receptivity. Abnormal decidualization of the endometrial stroma may clarify the possible association between adenomyosis and infertility. Our findings may be clinically useful for counseling and treatment of infertile adenomyosis patients. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the National Natural Science Foundation of China (82001523 and 82171639). The authors have no conflicts of interest to disclose. TRIAL REGISTRATION NUMBER: N/A.